2020
DOI: 10.1039/c9re00403c
|View full text |Cite
|
Sign up to set email alerts
|

Flow-controlled synthesis of gold nanoparticles in a biphasic system with inline liquid–liquid separation

Abstract: 4-Dimethylaminopyridine-stabilised gold nanoparticles are synthesised in a biphasic flow reactor system using organic/aqueous membrane separators and gas-permeable tubing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…In the wet chemical synthesis of nanostructured materials, directing a crystal facet by using a ligand or by selective etching of other facets has been widely investigated for preparing metal nanosheets and nanowires. [98,99] Very recently, Park et al has demonstrated a 9 nm-thick continuous Au (111) thin film by adopting the selective etching and the facet-directing ligand. [41] They converted a thermally-evaporated polycrystalline Au thin film to a single crystal Au (111) thin film.…”
Section: Pseudo-equilibrium Between Etching and Redepositionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the wet chemical synthesis of nanostructured materials, directing a crystal facet by using a ligand or by selective etching of other facets has been widely investigated for preparing metal nanosheets and nanowires. [98,99] Very recently, Park et al has demonstrated a 9 nm-thick continuous Au (111) thin film by adopting the selective etching and the facet-directing ligand. [41] They converted a thermally-evaporated polycrystalline Au thin film to a single crystal Au (111) thin film.…”
Section: Pseudo-equilibrium Between Etching and Redepositionmentioning
confidence: 99%
“…In the wet chemical synthesis of nanostructured materials, directing a crystal facet by using a ligand or by selective etching of other facets has been widely investigated for preparing metal nanosheets and nanowires. [ 98,99 ]…”
Section: Synthesis Of Isostructured Single Crystal Thin Filmsmentioning
confidence: 99%
“…Aggregation-induced emission (AIE) materials usually show the high luminous intensity and good bleaching resistance in the aggregate and solid states. [1][2][3] With the AIE material, we not only solve the problem of quenching induced by aggregation of traditional uorescent substances but also improve the contrast before and aer the aggregation-enhanced uorescence, which is very advantageous for improving the sensitivity of uorescence sensing and the quality of uorescence imaging. 4,5 In view of the above advantages, the development and application of uorescent materials with AIE characteristics have never stopped, and remarkable achievements have been made in uorescence sensing, biological imaging, drug delivery and release, medical diagnosis, and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, varied autonomous synthesis technologies have been developed to synthesize nanomaterials. For instance, gold nanoparticles and metal halide perovskite quantum dots have been reported to use batch and flow reactor technologies. These technologies are suitable for high-throughput chemical reactions, which can accelerate the synthesis process, decrease the experiment cost, and help investigate the synthesis mechanism.…”
Section: Introductionmentioning
confidence: 99%